The complex farm-level relationship between environmental performance and productivity: The case of carbon footprint of Lombardy farms. Issue 89 (November 2018) - Baldoni, Edoardo; Coderoni, Silvia; Esposti, Roberto
Highlights: The work empirically assesses the farm-level nexus between GHG and productivity. The use of micro data allows capturing farms performances' heterogeneity. Results confirm the productivity-emission nexus varies mainly per farm typology. Policy implications concern the possible differentiation of GHG targets at sub-sectoral level. Abstract: This paper aims to empirically estimate the relationship occurring between farm-level productivity and environmental performance. The productivity performance is measured by the Total Factor Productivity (TFP), while the environmental performance focuses on greenhouse gases (GHG) emissions expressed by the farms' Emission Intensity (EI). The relationship between the two performance indicators is investigated on a panel of Italian (Lombardy) farms observed from 2008 to 2013. The panel specification takes farm heterogeneity into account while the presence of autocorrelation in farm performance due to the typical time-dependence of agricultural production leads to a dynamic panel model estimated via GMM-SYS estimation. Results confirm that a EI-TFP nexus exists but it may significantly differ in direction and magnitude across farm typologies. Policy implications are finally derived.